Constraints in Adoption of Mushroom Production Enterprise - Gautam, Ashok Kumar; Singh, Prakash; Mishra, Dheeraj; Kumar, Arun; Singh , Abhishek Pratap (Indian Journal of Extension Education, 2014)
This study was an attempt to get the response regarding constraints faced by the respondents in adoption of mushroom  production enterprise in Haidargarh block of Barabanki district. The sample for the study comprised of 50 randomly  selected respondents trained by KVK in mushroom cultivation. The structured schedule was developed for data  collection. Study revealed that 'lack of proper marketing channel' was the most important constraint responsible for low  rate of adoption. 'Distantly located markets' and 'lack of government support' were the other major obstacles in this  process. 'Non availability of quality spawns' & 'risk involve due to perishable nature' were also observed as constraints by  the mushroom growers.
Keywords: Adoption; mushroom production; constraints